Cimetidine Does Not Inhibit 5-Aminolevulinic Acid Synthase or Heme Oxygenase Activity: Implications for Treatment of Acute Intermittent Porphyria and Erythropoietic Protoporphyria - Makiko Yasuda; Sangmi Lee; Lin Gan; Hector A. Bergonia; Robert J. Desnick; John D. Phillips (Biomolecules, 2023)
Acute intermittent porphyria (AIP) is characterized by acute neurovisceral attacks that are precipitated by the induction of hepatic 5-aminolevulinic acid synthase 1 (ALAS1). In erythropoietic protoporphyria (EPP), sun exposure leads to skin photosensitivity due to the overproduction of photoreactive porphyrins in bone marrow erythroid cells, where heme synthesis is primarily driven by the ALAS2 isozyme. Cimetidine has been suggested to be effective for the treatment of both AIP and EPP based on limited case reports. It has been proposed that cimetidine acts by inhibiting ALAS activity in liver and bone marrow for AIP and EPP, respectively, while it may also inhibit the hepatic activity of the heme catabolism enzyme, heme oxygenase (HO). Here, we show that cimetidine did not significantly modulate the activity or expression of endogenous ALAS or HO in wildtype mouse livers or bone marrow. Further, cimetidine did not effectively decrease hepatic ALAS activity or expression or plasma concentrations of the putative neurotoxic porphyrin precursors 5-aminolevulinic acid (ALA) and porphobilinogen (PBG), which were all markedly elevated during an induced acute attack in an AIP mouse model. These results show that cimetidine is not an efficacious treatment for acute attacks and suggest that its potential clinical benefit for EPP is not via ALAS inhibition.